Faktor Penentu Tingkat Minat Penggunaan QRIS pada Pelaku UMKM di Kabupaten Sleman - Purnomo, Yahya Agung; Pahlevi, Reza Widhar (Journal of Economics, Business, Accounting and Management, 2025)
This study aims to analyze the effect of transaction convenience, transaction security, and consumer preferences on the intention to use QRIS among micro, small, and medium enterprises (MSMEs) using a quantitative approach through a survey method. The research data were obtained from questionnaires distributed online to MSME actors in Sleman Regency, with the sample size determined using the Slovin formula and the measurement instrument based on a likert scale 5 poin. Data analysis was conducted using multiple linear regression, supported by t-tests, F-tests, and the coefficient of determination. The results indicate that transaction convenience, transaction security, and consumer preferences simultaneously influence the intention to use QRIS. Partially, transaction security and consumer preferences have a significant effect on the intention to use QRIS, while transaction convenience shows a weaker influence. These findings are consistent with the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), which emphasize the role of perceived usefulness, ease of use, and trust in technology adoption. This study is expected to provide practical contributions for MSME actors, local governments, and Bank Indonesia in encouraging increased adoption of QRIS.